Determining factors in the adoption of fintech of sharia in Indonesia: analysis of the effect of utaut2, Es-qual, and religiosity - Wibowo, Dedi; Hariri Bin Bakri, Mohammed (Edelweiss Applied Science and Technology, 2024)
This research examines the antecedents of actional desires towards using Islamic financial application among Indonesian customers. The objectives of the study empirically tested the expanded unified theory of acceptance and use of application (UTAUT2), ES-QUAL and religiosity as independent variables to explain the adoption of Islamic financial application in Indonesia. The method was quantitative. The 200 data are analyzed using the Partial least squares (PLS). The research results show that Effort Expectancy (EE), Social Influence (SI), Hedonic Motivation (HM), Esqual (ESQ), and Religiosity (RE) have a positive effect on Desire to Use Islamic Financial Application (IB). Furthermore, the Desire to Use Islamic Financial Application (IB) positively affects the Use Action of Islamic Financial Application (UB). In addition, only gender (GE) can weaken the influence of hedonic motivation and habit on the Desire to Use Islamic financial application. The influence actional desires to use Islamic financial application because of the lack of research in this domain in Indonesia, especially considering the context of religiosity and combining the concepts of UTAUT2 and ESQUAL. This research contributes to the service quality literature by identifying E-SQ and confirming its effectiveness in FinTech adoption. This can also enhance to the development of understanding financial concepts.